Treatment of irregular heartbeats - Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association, 2020)
Arrhythmias, as the name suggests, are abnormal rhythms of the heart. It occurs either as due to an abnormality in the formation of impulse or due to an abnormality in the impulse conduction, or both. Patients with arrhythmia often present with palpitations or an awareness of their own fluttering heartbeat, racing heartbeat, chest pain or shortness of breath.